ABOVE THE TIME. BISHOP MIKHAIL (GRIBANOVSKY): AN ATTEMPT OF HIS THEOLOGICAL PORTRAIT - PRIEST PAVEL KHONDZINSKY (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2009)
Many deep processes in the Russian spiritual tradition in the last quarter of the XIX c. — movement for the restoration of the patriarchate, renewal of the parish life, aspiration to attach to the theological truth its direct vital importance, search for a new Christian philosophy — are connected with the name of bishop Mikhail (Gribanovsky). Yet his name and heritage even now are far from being well-known. In the article the author attempts to off er a theological portait of the bishop, in other words, to present to a reader an essay on the formation of his personality and his theological thought in their inner organic interrelation